Therapeutic Itineraries of Female Migrants from Bolivia in the City of Buenos Aires - Buzzi, Pablo Andrés (2020)
This paper aims to describe and analyze the therapeutic itineraries of female migrants from Bolivia residing in two neighborhoods of Buenos Aires, “Bajo Flores” and “Villa 31”. Qualitative methodology, using techniques of interviews and focus groups, oriented the investigation of health care strategies. As a principle result, we identified the  articulation of various health care strategiess, particularly that of frequent consultation of pharmacists as substitution for physicians, be this a form of avoiding the barriers and obstacles of access to the public health system or as an alternative to previous therapeutic failures. In addition, the barriers that these women encounter when trying to access care in the public health system are described. Finally, we observed that the circulation of information among family members, neighbors, friends and "countrymen" is the most frequent means of accessing knowledge about the available care alternatives in each territory.